The Travel book a journey through every country in the world - Bain, Carolyn; Bindloss, Joe; Brash, Celeste; Clammer, Paul; Fitzpatrick, Mary; Gourlay, Will; Ham, Anthony; Mayhew, Bradley; McCarthy, Carolyn; Phillips, Matt; Reid, Robert; St Louis, Regis; et al. (Lonely Planet, 2013)
Presents a look at the history, culture, festivals, and sports of the Philippines, with recommendations on hotels, restaurants, shopping, entertainment, and historical sites.